Salt stress and its eco-friendly management using biostimulants in grain legumes: a review - Narayan Singh; Vasudha Maurya; Kriti Gupta; Indu Sharma; Ashutosh Sharma; Rahul Kumar (Discover Agriculture)
Abstract Grain legumes are a rich source of dietary proteins and hence are essential for achieving food and nutritional security, worldwide. Grain legumes are negatively affected by salt stress, which results in decreased growth, yield, productivity, and other financial losses. Salt stress causes severe phytotoxicities, like specific ion toxicities, hormonal and nutritional imbalances, disruptions of stomatal conductance, and alterations in leaf water potential and rate of photosynthesis. To enhance agricultural productivity under salt stress conditions, several ecofriendly methods have been tried recently. Out of these, the use of biostimulants gained particular attention due to their ease of availability and high-stress ameliorative potential. It includes the use of non-microbial biostimulants like humic acid and seaweed extracts (SWE), as well as microbial biostimulants like mycorrhiza, plant growth-promoting and nitrogen-fixing bacteria, which promote plant growth and development. Biostimulants successfully alleviate salt stress-induced toxicities in legumes, when introduced either alone or in combination with other macro- or microorganisms in the soil. In response to salinity, plants raise their cellular levels of osmolytes (proline and glycine betaine) and polyamines, as well as phytohormones. The application of biostimulants in grain legumes alleviates the salt stress-induced toxicity by improving the seed germination, seedling growth, rate of photosynthesis, nitrogen fixation, absorption and uptake of minerals, grain development, yield, ROS homeostasis and osmoregulation. Many of the reviews have lacked the assessment of the effect of these ecofriendly biostimulants on mitigation of salt stress in grain legumes. The development of integrated, eco-friendly and sustainable use of various biostimulants and their mode of action in managing salt stress in legume production is discussed in the present review.